Coccidian parasites from birds at rehabilitation centers in Portugal, with notes on Avispora bubonis in Old World - Sergian Vianna Cardozo; Bruno Pereira Berto; Inês Caetano; André Thomás; Marcos Santos; Isabel Pereira da Fonseca; Carlos Wilson Gomes Lopes (Revista Brasileira de Parasitologia Veterinária, 2019)
Abstract Portugal has some rehabilitation centers for wild animals, which are responsible for the rehabilitation and reintroduction of birds, among other animals, into the wild. Coccidian parasites of these wild birds in rehabilitation centers are especially important because these centers can introduce coccidian species into new environments through the reintroduction of their respective hosts. In this context, the current study aimed to identify intestinal coccidia from wild birds at two rehabilitation centers for wild animals located in two municipalities of Portugal. Eighty-nine wild birds of 9 orders and 11 families were sampled, of which 22 (25%) were positive for Coccidia. Avispora spp. were found in raptors. Sporocysts of Sarcocystinae subfamily were recovered from owls. An Isospora sp. was found in Turdus merula Linnaeus, 1758, and an Eimeria sp. was found in Fulica atra Linnaeus, 1758. Among the coccidian species, Avispora bubonis (Cawthorn, Stockdale, 1981) can be highlighted. The finding of this species indicates that transmission of coccidians from the New World to the Old World may be occurring, potentially through dispersion by Bubo scandiacus (Linnaeus, 1758) through Arctic regions or by means of anthropic activities, and/or through other unknown mechanisms.